Struktur Komunitas Fitoplankton sebagai Dasar Pengelolaan Kualitas Perairan Pantai Mangrove di Tapak Tugurejo Semarang - Lathifah, Nurul; Hidayat, Jafron Wasiq; Muhammad, Fuad (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Phytoplankton has of important role in water as of base of the food chain this is also can service a bioindicator the pollution of waters. This study aims to assess the phytoplankton community structure in Tapak Semarang, assessing the level of fertility of inshore mangrove community, and to assess the water quality of inshore. Samples were take in is in the mangrove region of Tapak Semarang. This study was conducted in May 2016 (rain season) and in September 2016 (dry season). Selection of the stations were based on different environmental conditions in the research include the pond and public waters in the waters of coastal mangrove the soles of Semarang. Analysis of index diversity, index evennes and index saprobik. The results showed that the spesies of phytoplankton obtained during the study on mangrove coastal waters Tapak Tugurejo Semarang were 13 species (rainy season) and 25 species (dry season). The most common species of phytoplankton found in all stations wereCerataulina bergonii, Nitzhcia sp, Rhizosolenia spp, Synedra ulna, Netrium digitus, Gloeotrichia echinulata, and Oscillatoria Formosa. Index of species diversity (Hâ€™) that exist in mangrove coastal waters Tapak Tugurejo Semarang were in the range of 0.73 to 1.95 low to moderate with low to moderate quality of stabilities during the rainy season. Mean while in the dry season of high species diversity index in the range of 2.24 to 2.82 which indicated stability of the ecosystem was low to moderate. The value of evennes index (e) ranged from 0.66 to 0.97 during the rainy season, and 0.90 to 0.94 in the dry seasons these indices illustrated that each station has a moderate to high similaritas. In term of saprobitas level it was at Oligosaprobik state to Î²-Meso/Oligosaprobik describe very mild to light polluted. The quality of mangrove coastal waters based DO, temperature, salinity and pH are still good for fish farming.Â Keywords: community structure, phytoplankton, Tapak, Tugurejo, Semarang..Â